Efectos de las actividades de gráfico plástica y la coordinación viso manual en niños de cinco años de edad de la institución educativa inicial N° 048 Barranca 2024 - Soto Marin, Cledy (2025)
To determine the effect of the application of graphic-plastic activities on visuomotor coordination in five-year-old children at Initial Educational Institution No. 048 Barranca 2024, the type of research study employed was a quantitative approach with an experimental design. The study population consisted of five-year-old children from Initial Educational Institution No. 048 Barranca 2024, totaling 46 children. The data collection technique used was observation, conducted with an observation guide validated by three subject matter experts. Reliability was established using Cronbach's Alpha method. The results obtained through the Student’s t-test for independent samples yielded a statistical value of t_c = 6.322 with a p-value of p = 0.000. Using a significance level of alpha = 0.05, it was evident that there were significant differences between the experimental and control groups regarding the development of visuomotor coordination after the application of graphic-plastic activities. It was concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This means that the application of graphic-plastic activities has significant effects on the development of visuomotor coordination in five-year-old children.